一种基于改进Prandtl-Ishlinskii模型的压电驱动器复合控制方法 (2023)
本发明属于压电驱动器控制的技术领域，具体公开了一种基于改进Prandtl-Ishlinskii模型的压电驱动器复合控制方法，包括步骤1：采用基于Prandtl-Ishlinskii改进的MRAPI迟滞逆模型描述压电驱动器的迟滞非线性特性；步骤2：直接逆模型建模方式获得MRAPI迟滞逆模型；步骤3：辨识出MRAPI迟滞逆模型的参数；步骤4：辨识后的MRAPI迟滞逆模型与PID反馈控制器结合控制压电驱动器。本发明取得的有益效果：保留了Prandtl-Ishlinskii模型的核心结构，待辨识参数少，辨识过程简单，精确地描述压电驱动器的动态迟滞过程，简化逆模型的求解过程，补偿了系统的迟滞非线性，减小建模误差和外部干扰，提高系统的鲁棒稳定性，实现压电驱动器的高精度轨迹跟踪控制。 The invention belongs to the technical field of piezoelectric actuator control, and particularly discloses a piezoelectric actuator composite control method based on an improved Prantl-Ishlinskii model, and the method comprises the steps: 1, describing the hysteresis nonlinear characteristics of a piezoelectric actuator by employing an improved MRAPI hysteresis inverse model based on Prantl-Ishlinskii; 2, obtaining an MRAPI hysteresis inverse model in a direct inverse model modeling mode; 3, identifying parameters of the MRAPI hysteresis inverse model; and 4, combining the identified MRAPI hysteresis inverse model and a PID feedback controller to control the piezoelectric act